Inbreeding in sugarcane varieties - Marcelo de Almeida Silva (Ciência Rural, 2011)
Sugarcane species are allogamous, i.e. selfing is expected to reduce plant vigor. This study was undertaken to obtain and evaluate first-generation inbred lines that may be used for further crosses and determine the extent of inbreeding depression in sugarcane. In this research, 26 parental varieties were self-pollinated to obtain about 19,000 seedlings. Results showed that it is possible to segregate different traits in a given variety and find lines with promising outcome for all assessed characteristics. The soluble solids segregation observed in low and even high-Brix varieties increases the possibility of quick improvement in this trait. Self-pollination did not produce a general loss in yield traits such as soluble solids, stalk number and stalk diameter in any of the 26 varieties, but both stalk height and stalk weight showed strong inbreeding depression. Selfing-derived clones can be used to produce hybrid vigor in crossings.